Effective Christian Leadership is Based on Faith and the Vision of God - Patar Lestari Nababan; Tetti Manullang (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research examines the importance of Christian Leadership in internship campuses such as at STT ABDI SABDA Deli Serdang Regency, that effective leadership is a sustainable factor such as internal and external factors, a Christian leader must be based on the vision and faith of God. Christian vision is a gift from God that is depicted in the inner self of a leader to carry out His eternal work. A living faith based on the living and eternal word of God is the basis for the vision and ethics of Christian leadership. Effective Christian leadership must be based on the characteristics of God and have holiness of life and a spirit of fear of God. A good Christian leader must have absolute truth as a basic principle for achieving success. The vision and ethics of Christian leadership must be centered on God through the living and eternal word of God, and become the basis for the vision and ethics. Method: Using a literature research approach and a descriptive qualitative methodology, data is gathered from journals, books, interviews, and documents that are relevant to the subject of study. Findings: First, what sort of Christian leadership is it possible for STT ABDI SABDA to adopt?. Second, the factors that influence a Christian leader. Third, ways to develop faith and vision of God for a Christian leader. Fourth, characteristics of an effective leader. Fifth, faith and vision of God which can help effective Christian leadership. Conclusion: With the existence of Christian Leadership, we know that not everyone has an important role in carrying out the spirit of discipline as stated in the Results and discussion chapter